The role of CIAT in the international improvement of cassava: The agricultural economics input - Pinstrup-Andersen, Per (International Center for Tropical Agriculture, 1972)
Suggested objectives of the agricultural economics program at CIAT are to collaborate in the allocation of research resources, improve the economic efficiency of cassava production and marketing, estimate the overall socioeconomic consequences of the adoption of improved technology in production and marketing, and guide private and public investment and public policy with respect to cassava. Specific areas of research needed include the identification of major bottlenecks in production, marketing and consumption and estimation of the relative economic importance of each; the estimation of production costs under various management systems; the estimation of economic losses during transportation and storage under different marketing systems; and the analysis of present and future demand for cassava as well as the implications of expanded production. (CIAT)